P122 What do patients with lupus and Sjögren's syndrome know about cardiovascular risk?. (23rd March 2020) - Navarro, Elvira Chocano; Robinson, George; Waddington, Kirsty; McDonnell, Thomas; Wincup, Chris; Martin-Gutierrez, Lucia; Maggio, Annalisa; McLoughlin, Eve; Rosser, Lizzy; Isenberg, David; Kalea, Anastasia; Ciurtin, Coziana; et al.
Abstract : Background: Cardiovascular risk (CVR) is the leading cause of mortality in patients with lupus. Understanding increased CVR in autoimmune rheumatic diseases could improve management of risk in patients. This event aimed to explore patient opinions about CVR and potential CVR treatment options. Methods: We hosted a patient event promoted through social media, relevant charities, hospitals and research groups. 13 patients with lupus and/or Sjögren's syndrome attended and were asked about CVR using a questionnaire (14 questions) and round table discussion with patients, researchers, clinicians and dietitians. Results: Sixty percent of patients were aware of the increased CVR associated with autoimmune rheumatic disease and 60% stated that their doctor had spoken to them about this risk. 73% thought that it was important for them to be aware of this increased CVR. When asked about medication to reduce CVR, no patients wanted to take a statin (lipid lowering drug), however, 70% of patients would take statins if advised to do so by their doctor. Conversely, respondents were more positive about using diet or taking a dietary supplement to reduce CVR; 71% would change their diet and 57% would take a supplement either on their own accord or on advice from health professionals. Some patients had already made changes to their diet to reduce their CVR, including reducing fat and increasing fruit and vegetable consumption. All attendees were prepared to participate in a clinical study using diet modification strategies, having vascular scans to assess atherosclerosis and provide blood samples for CVR research in lupus/Sjögren's syndrome. Conclusion: This multidisciplinary event successfully gathered patient information regarding CVR. The opinions and comments provided evidence that patients support further research in cardiovascular studies and a preference to changing their diet or take a supplement, whilst avoiding medication, to reduce their CVR.